Method for producing artificial vitreous fibers

By directly adding aluminum particles or aluminum blocks to the melt pool or above it, the problem of excessive shrinkage rate of MMVF products in gas furnace manufacturing MMVF products under high temperature conditions is solved, and better fire resistance and insulation performance are achieved, while maintaining environmental and economic benefits.

CN119504116APending Publication Date: 2025-02-25ROCKWOOL AS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411516920.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2020-01-30
Filing Date
2021-01-29
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Artificial glass fiber (MMVF) products made with gas furnaces shrink too high under high temperature or fire conditions, resulting in the formation of thermal bridges and insulation gaps, affecting the performance and safety of the product.

Method used

By directly adding aluminum particles or aluminum blocks to or above the melt pool in a cyclone furnace, the premature or excessive oxidation of metal aluminum is avoided, thereby improving process efficiency and improving the performance of MMVF.

Benefits of technology

It effectively reduces the shrinkage rate of MMVF products under high temperature conditions, improves the product's fire resistance and insulation performance, and maintains environmental and economic benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119504116A_ABST
    Figure CN119504116A_ABST
Patent Text Reader

Abstract

Methods of making artificial vitreous fibers (MMVFs) are provided, including incorporating metallic aluminum into a mineral aggregate, in favor of reducing shrinkage of consolidated MMVF products.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This patent application is a divisional application of the patent application with application number 2021800213504, application date January 29, 2021, and invention name “Method for manufacturing artificial glass fiber”. Technical Field

[0002] The present invention relates to a method for producing man-made vitreous fibers (MMVF) by melting mineral materials using a gas furnace. Background Art

[0003] The present invention relates to methods of making MMVF and consolidating MMVF products (e.g., insulation products). Typically, a mineral raw material (ore) having a desired overall chemical composition is melted in a furnace, the mineral melt is removed and fed to a fiberizing device, such as an external or internal centrifugal device, and the fibers are collected, further processed if necessary, and formed into insulation wool, usually with a binder.

[0004] In the prior art, electric furnaces or coal-fired furnaces are generally used.

[0005] Some electric furnaces can be supplied with a combination of gas fuel and combustion gas.

[0006] It is desirable to switch from coal-fired furnaces to gas-fired furnaces for environmental benefits. For example, gas fuel is available as biogas, which can be carbon neutral. In addition, gas fuel may be cheaper than coal due to carbon taxes, and gas-fired furnaces require less exhaust scrubbing or other emission reduction systems than coal-fired furnaces.

[0007] When coal-fired furnaces are used to produce the mineral melt for the fibers, the resulting consolidated MMVF products shrink within acceptable limits when exposed to heat or fire conditions, typically with an area shrinkage of less than 40%. Shrinkage should be avoided or at least reduced as much as possible, as thermal bridges and insulation gaps can form when consolidated MMVF products shrink in high temperature situations.

[0008] The inventors have found that when using MMVF from a gas fired furnace, the consolidated MMVF product shrinks to a level higher than acceptable.

[0009] This issue must be addressed to realize the environmental benefits of natural gas as a fuel over coal while maintaining product performance and safety. Summary of the invention

[0010] The inventors have solved the shrinkage problem of consolidated MMVF products from gas furnaces using the method of claim 1.

[0011] The metallic aluminum can be in the form of aluminum pellets. The aluminum pellets primarily comprise metallic aluminum with an outer layer of aluminum oxide due to exposure to oxygen. The aluminum pellets can comprise 45% by weight of metallic aluminum to 100% by weight of metallic aluminum, such as 45% by weight to 99.5% by weight or 45% by weight to 99% by weight of metallic aluminum.

[0012] In the process, it is preferred to inject the aluminum pellets directly into or just above the molten pool in the furnace. Otherwise, the metallic aluminum in the aluminum pellets will be over-oxidized before it melts and comes into contact with the Fe2O3, thereby eliminating the thermal and redox benefits of having the metallic aluminum as part of the ore charge. Injecting the aluminum pellets directly into or just above the molten pool is particularly preferred in cyclone furnaces, with the other mineral components being melted in the cyclone, unlike other types of furnaces where all of the solid batch material may be melted in the molten pool.

[0013] Another suitable form of metallic aluminum is one or more blocks. The block can be in any suitable form, such as a rod, a strip, a lump or other shape. The block can contain from 45% to 100% by weight of metallic aluminum. The metallic aluminum in the shape of a rod or other block can be directly inserted into the mineral melt in the furnace. This method avoids excessive or premature oxidation of the metallic aluminum before mixing with the mineral molten pool, thereby improving process efficiency. The aluminum block used in the present invention may mainly include metallic aluminum, which forms an outer layer of aluminum oxide due to exposure to oxygen. Without wishing to be bound by theory, it is believed that the aluminum block directly contained in the melt or added to the furnace a short distance above the molten pool melts and forms droplets, which interact with the rest of the mineral melt to form a reducing environment when the metallic aluminum is oxidized. However, the site where the aluminum block is added to the furnace is not limited, for example, the aluminum block can be inserted into the top of the furnace.

[0014] In terms of the content of metallic aluminum, metallic Al preferably accounts for 0.1 to 0.5 wt % of the total ore, for example, 0.2 to 0.4 wt % or about 0.2 wt % of the total ore.

[0015] Another benefit of including metallic Al directly in or directly above the mineral bath in the furnace is that oxidation of Al is more exothermic than burning coal, so an additional heating effect due to the addition of metallic Al is observed in the present invention.

[0016] When a cyclone furnace is used, the aluminum pellets are preferably added directly into the molten bath, or just above the molten bath. Preferably, addition is via a burner or lance. Preferably, an oxyfuel burner with a central tube for transporting the aluminum pellets is used.

[0017] Aluminum pellets may be added to locations above the bath surface and within 50 cm of the bath surface, preferably 30 cm.

[0018] As a raw material component containing only aluminum particles, the aluminum particles can be added alone. Alternatively, it can be pre-mixed with a filler and the mixture of aluminum particles and filler is added to the furnace as a mixed raw material component. Suitable fillers include various raw materials that can be used as additional raw materials. For example, the aluminum particles can be mixed with filtered fine powder (i.e., fine particle raw material extracted from the exhaust filter of the cyclone furnace) before being injected into the cyclone furnace. In the mixture with the filler, the suitable percentage of aluminum particles is 1% to 90%, such as 10% to 70%, such as 15% to 50%. Using a mixture of aluminum particles and other raw materials can improve the dosage control of metallic aluminum in the process.

[0019] The aluminum particles are well mixed with the mineral melt due to the similar densities of the melt and metallic aluminum.

[0020] The particle size (average particle size, wherein the particle size adopts the maximum dimension of the particle, whether the particle is spherical or not) of the aluminum particles may be no greater than 15 mm, such as less than 10 mm, such as less than 5 mm. In a preferred embodiment, the particle size (average particle size, wherein the particle size adopts the maximum dimension of the particle, whether the particle is spherical or not) of the aluminum particles may be no greater than 3 mm, such as less than 2 mm, such as less than 1 mm.

[0021] The residence time of the particulate mineral material and the mineral melt in a cyclone furnace is lower than in other types of mineral smelters, so fast reaction kinetics are important in this process.

[0022] When using a canister furnace, larger blocks of aluminum metal can be used than are available with a cyclone furnace.

[0023] The total ore charge, mineral melt and MMVF should have an iron oxide content of at least 3% by weight.

[0024] In the present invention, the mineral raw material may contain 0.1 wt% to 0.5 wt% of metallic aluminum.

[0025] In a preferred embodiment, the MMVF has the following element contents, expressed in wt. % of oxides:

[0026] SiO2: at least 30, 32, 35 or 37; not more than 51, 48, 45 or 43

[0027] CaO: at least 8 or 10; not more than 30, 25 or 20

[0028] MgO: at least 2 or 5; not more than 25, 20 or 15

[0029] FeO (including Fe2O3): at least 4 or 5; not more than 15, 12 or 10

[0030] FeO+MgO: at least 10, 12 or 15; not more than 30, 25 or 20

[0031] Na2O+K2O: 0 or at least 1; not more than 10

[0032] CaO+Na2O+K2O: at least 10 or 15; not more than 30 or 25

[0033] TiO2: 0 or at least 1; not more than 6, 4 or 2

[0034] TiO2+FeO: at least 4 or 6; not more than 18 or 12

[0035] B2O3: 0 or at least 1; not more than 5 or 3

[0036] P2O5: 0 or at least 1; not more than 8 or 5

[0037] Others: 0 or at least 1; not more than 8 or 5.

[0038] The fibers preferably have a sintering temperature above 800°C, more preferably above 1000°C.

[0039] The MMVF produced by the method of the present invention preferably has the following composition, in wt %:

[0040] SiO2 35 to 50

[0041] Al2O3 12 to 30

[0042] TiO2 up to 2

[0043] Fe2O3 3 to 12

[0044] CaO 5 to 30

[0045] MgO up to 15

[0046] Na2O 0 to 15

[0047] K2O 0 to 15

[0048] P2O5 up to 3

[0049] MnO up to 3

[0050] B2O3 is as high as 3.

[0051] Another preferred composition of MMVF is as follows, in wt %:

[0052] SiO2 39% to 55%, preferably 39% to 52%,

[0053] Al2O3 16% to 27%, preferably 16% to 26%,

[0054] CaO 6% to 20%, preferably 8% to 18%,

[0055] MgO 1% to 5%, preferably 1% to 4.9%,

[0056] Na2O 0% to 15%, preferably 2% to 12%,

[0057] K2O 0% to 15%, preferably 2% to 12%,

[0058] R2O(Na2O+K2O) 10% to 14.7%, preferably 10% to 13.5%,

[0059] P2O5 0% to 3%, preferably 0% to 2%,

[0060] Fe2O3 (total iron) 3% to 15%, preferably 3.2% to 8%,

[0061] B2O3 0% to 2%, preferably 0% to 1%,

[0062] TiO2 0% to 2%, preferably 0.4% to 1%,

[0063] Others 0% to 2.0%.

[0064] The composition may be suitably used as a fiberizing device in conjunction with an internal centrifugal device.

[0065] The preferred range of SiO2 is 39% to 44%, especially 40% to 43%. The preferred range of CaO is 9.5% to 20%, especially 10% to 18%.

[0066] The Al2O3 content is preferably between 16% and 27%, preferably greater than 17% and / or preferably less than 25%, and the sum of SiO2 and Al2O3 is preferably between 57% and 75%, preferably greater than 60% and / or preferably less than 72%. The amount of alkali metal (sodium and potassium) oxides (R2O) in the fiber composition is preferably relatively high, but limited to 10% to 14.7%, preferably 10% to 13.5%, wherein the amount of magnesium oxide is at least 1%.

[0067] Preferably, the Al2O3 content is 17% to 25%, in particular 20% to 25%, in particular 21% to 24.5%, especially about 22% to 23% or 24% by weight. Advantageously, the magnesium oxide content is at least 1.5%, in particular 2%, preferably 2% to 5%, particularly preferably >2.5% or 3%.

[0068] In the case of an Al2O3 content of at least 22%, the amount of magnesium oxide is preferably at least 1%, advantageously about 1% to 4%, preferably 1% to 2%, and in particular 1.2% to 1.6% by weight. In order to keep the liquidus temperature sufficiently low, the Al2O3 content is preferably limited to 25%. When the Al2O3 content is a lower amount, for example, about 17% to 22%, the amount of magnesium oxide is preferably at least 2%, in particular about 2% to 5%.

[0069] The total amount of Fe and Mg oxides is important in controlling the shrinkage of MMVF insulation. In addition, the ratio of Fe(II):Fe(III) affects the insulation performance of MMVF under fire conditions, where oxidation of Fe(II) to Fe(III) is a favorable process.

[0070] Advantageously, the ratio of Fe(II):Fe(III) of the fibers is higher than 2, for example higher than 3. The proportion of Fe(3+) in the MMVF before the fiberizing step is generally less than 5%, preferably less than 3%, based on the total Fe content in the melt. This helps to prevent shrinkage.

[0071] The amounts of Fe(2+) and Fe(3+) can be determined using the formula described in “The ferric / ferrous ratio in basalt melts at different oxygen pressures” (Helgason et al., Hyperfine Interact., 45 (1989), pp. 287 to 294). Method determination.

[0072] The total iron in the entire melt or fiber composition is calculated as Fe2O3 based on the total oxides in the melt or fiber. This is the standard method of quoting the amount of iron present in such MMVF, charge or melt. The actual weight percentages of FeO and Fe2O3 present will vary depending on the iron oxide ratio and / or redox state of the melt. For example:

[0073]

[0074] Table 1

[0075] Thus, one skilled in the art will appreciate that the actual weight percent of iron oxide present will depend on the ratio of Fe(2+) to Fe(3+).

[0076] The mineral melt formed in the process may be formed into an MMVF using any suitable method, such as internal centrifugation or external centrifugation. Suitable fiber spinning methods and apparatus are known to those skilled in the art.

[0077] The method of the present invention may further comprise consolidating the MMVF to form a consolidated product comprising the MMVF. The consolidated product may be used in many applications, including fireproof insulation products. In such applications, reducing shrinkage is particularly advantageous because it reduces the risk of thermal bridges or insulation gaps forming in critical situations.

[0078] The total amount of iron oxide in the fibres may be a mixture of FeO and Fe2O3 but, by convention, is quoted herein as Fe2O3.

[0079] The method of the invention can be advantageously used with all types of gas fired furnaces for melting mineral feedstocks. Preferred types of gas fired furnaces are pot furnaces and cyclone furnaces. Heating from the combustion of the gaseous fuel can be supplemented by the use of electrode heating, such as Joule heating from immersed molybdenum electrodes.

[0080] When aluminum pellets are used, they are preferably added to the molten pool or directly above the molten pool to avoid premature oxidation of the metal Al contained in the pellets. A burner or a lance may be used to inject the aluminum pellets into the furnace. An oxygen-fuel burner with a central tube for transporting the aluminum pellets is preferably used.

[0081] The aluminum is preferably added to the bath in bulk form separately from the other mineral components. In a cyclone furnace, the other mineral components are usually in granular form and melted in the cyclone, while the aluminum bulk is primarily melted in the bath.

[0082] The particle size (average particle size, where the particle size adopts the maximum dimension of the particle, whether or not the particle is spherical) of the aluminum particles may be no greater than 15 mm, such as less than 10 mm, such as less than 5 mm. In a preferred embodiment, the particle size (average particle size, where the particle size adopts the maximum dimension of the particle, whether or not the particle is spherical) of the aluminum particles may be no greater than 3 mm, such as less than 2 mm, such as less than 1 mm.

[0083] Aluminum particles typically contain 50 to 95 wt% metallic Al, such as about 90 wt% metallic Al. Since the surface area to volume ratio of the bulk is lower than that of small particles, the surface oxidation of Al is less, so the Al bulk can contain up to 100 wt% metallic Al, such as up to 99 wt% metallic Al.

[0084] Since the mineral melt and metallic aluminum have similar densities, the solid aluminum particles added directly to the molten pool mix well with the mineral melt.

[0085] The gaseous fuel may be natural gas, methane, propane, biogas (methane derived from biological sources) or any other suitable carbon-containing gaseous fuel. Preferably, the gaseous fuel is natural gas or biogas, most preferably biogas.

[0086] In this method, the combustion gas contains oxygen to complete the combustion of the fuel. The combustion gas can be air in its natural composition, pure oxygen or oxygen-enriched air.

[0087] As is known, the raw materials used as the remainder of the ore charge can be selected from a variety of sources. These include basalt, diabase, nepheline syenite, cullet, bauxite, quartz sand, limestone, borax, sodium tetraborate, dolomite, soda, olivine sand, potash. Waste materials can also be used.

[0088] MMV fibers can be made from mineral melts in a conventional manner. Typically, they are made by a centrifugal fiberization process.

[0089] For example, the fibers can be formed by a spinning rotor process, in which they are thrown outward through holes in the spinning rotor. The melt is fiberized by the spinning rotor technology (sometimes also called internal centrifugation). Before being directed to the spinning rotor, the melt preferably has a temperature in the range of 1260° C. to 1300° C. at the end of the feeder channel. When the melt is transferred from the feeder channel to the inner part of the spinning rotor, it is preferably cooled down so that the temperature of the melt when flowing through the holes of the spinning rotor is in the range of 1150° C. to 1220° C.

[0090] The viscosity of the melt in the spinning rotor is in the range of 50 Pa.s to 400 Pa.s, preferably in the range of 100 Pa.s to 320 Pa.s, and more preferably in the range of 150 Pa.s to 270 Pa.s. If the viscosity is too low, fibers of a desired thickness cannot be formed. If the viscosity is too high, the melt does not flow through the holes in the spinning rotor at an appropriate discharge rate, which may cause clogging of the holes in the spinning rotor.

[0091] The melt is preferably fiberized by a spinning rotor process at a temperature between 1160° C. and 1210° C. At the spinning temperature, the viscosity of the melt is preferably in the range of 100 Pa.s to 320 Pa.s.

[0092] In another fiber forming process, the melt may be thrown from a rotating disk and fiber formation may be promoted by passing a jet of injected gas through the melt.

[0093] In a preferred method, fiber formation is performed by pouring the melt onto the first rotor in a cascade spinneret. In this case, the melt is preferably poured onto the first of a set of two, three or four rotors, each rotating about a substantially horizontal axis, whereby the melt on the first rotor is primarily thrown onto the second (lower) rotor, although some may be thrown off the first rotor in the form of fibers, and the melt on the second rotor is thrown off in the form of fibers, although some may be thrown toward the third (lower) rotor, and so on.

[0094] MMVF can be collected and consolidated to form a consolidated product comprising MMVF. Typically, such products may include additional ingredients, such as a binder, wherein MMVF is the main ingredient. The fibers produced by the spinning process are preferably collected on a conveyor belt. The binder can be applied to the MMVF in the fiberization process or after fiberization. The binder can be applied by spraying the MMVF. The conventional type of binder used with rock wool fibers can be used. The binder is then cured to produce a final product. The MMVF with a binder is typically cured in a curing oven, typically by a hot air stream. A hot air stream can be introduced into the MMVF with a binder from below or above or from alternating directions in different regions in the length direction of the curing oven. After curing, the cured binder composition bonds the fibers to form a structurally adhered fiber matrix.

[0095] The MMVF may be consolidated after collection, for example by cross-lapping and / or longitudinal compression and / or vertical compression in a known manner. Typically consolidation occurs before the binder cures.

[0096] The MMVF produced by the method of the present invention and the MMVF of the present invention have excellent fire resistance at 1000°C. The MMVF can be made into products for any conventional application of MMVF (e.g., sound insulation or heat insulation or fire protection). Such products include insulation products such as insulation wool, particles, boards, rolls, pipe sections, and other products such as tiles and loose fibers. The product can be used in high temperature environments, such as at least 400°C to as high as 1000°C.

[0097] The product may have any density known in the art for the relevant application. For example, the density may be 20 kg / m 3 Up to 1200kg / m 3 In the range of 20kg / m 3 Up to 300kg / m 3 In the range of 20kg / m 3 Up to 150kg / m 3 All product types have advantages in terms of shrinkage, but it has been observed that when the density of the product is relatively low (e.g. not more than 50 kg / m 3 ), a particularly good reduction in shrinkage can be seen. BRIEF DESCRIPTION OF THE DRAWINGS

[0098] Figure 1 is a schematic diagram of a cyclone furnace used in an embodiment of the present invention. DETAILED DESCRIPTION

[0099] Figure 1A cyclone furnace 1 is shown, which comprises a cylindrical top, a frustoconical bottom and a cylindrical base. Preheated mineral material (with or without metallic aluminium) is introduced into the cyclone furnace through a mixed mineral material conduit 3. Fuel is introduced through conduit 2. The mineral material is introduced together with combustion air through conduit 4 and secondary air, which is provided in a compressed air supply 5 and introduced into the cyclone furnace through a lance (not shown) to ensure a thorough mixing of the fuel with the combustion air and to maintain a circulating motion of the combustion gases and suspended matter within the cyclone furnace 1. The combustion gases and suspended matter are respectively introduced through Figure 1 A small amount of combustion gas and fuel is diverted from the main feed to the top of the cyclone furnace to the bottom of the cyclone furnace by the route shown in 6 and 7. Secondary fuels such as natural gas are also injected into the base of the cyclone furnace through supply 8, such as Figure 1 As shown in 8.

[0100] The fuel is burned in a cyclone furnace in a combustion gas which is preferably pure oxygen or oxygen-enriched air, thereby melting the ore.

[0101] Aluminium metal is preferably added directly to the cyclone furnace 1. Aluminium metal may be provided as aluminium pellets and added via an oxyfuel burner at position 8. The remainder of the ore is provided by a silo 19 and preheated as described above. Alternatively, aluminium metal may be provided in block form, in the form of rods, bars or briquettes. Aluminium in block form is preferably added to the cyclone furnace separately from the granular mineral feedstock and may be added directly to the molten bath. Smaller aluminium chunks may be injected into the furnace via the burner port. Larger aluminium chunks may be injected into the furnace from an inlet at the top of the furnace. Bulk aluminium may be blown or otherwise injected directly into the molten bath at the base of the furnace; it may be preferred to minimise oxidation of aluminium in the gases circulating in the furnace, thereby maximising the effect of the interaction of the aluminium metal with the other mineral components.

[0102] The ore material is melted in the cyclone furnace 1 and the resulting ore melt is collected in the base area of ​​the cyclone furnace 1 and leaves the furnace through the outlet 9. The exhaust gases generated by the combustion of the fuel are fed through the flue 10 at the top of the circulating combustion chamber to the first duct 11, where the exhaust gases are used to heat the ore material. The exhaust gases then flow to the first cyclone preheater 12, where they are separated from the ore material. From the first cyclone preheater 12, the exhaust gases flow through the second duct 14 to the second cyclone preheater 13. After the second cyclone preheater 13, the exhaust gases flow through the duct 15 to the dust cyclone 16 and enter the chamber 17, where indirect heat exchange with the combustion gases takes place to preheat the combustion gases. The exhaust gases are then treated so that they can be safely discharged to the atmosphere through, for example, a filter 18 and a desulfurization device.

[0103] Some of the mineral material may be carried away with the off-gas from the second cyclone preheater 13 via duct 15. This mineral material is separated from the off-gas in the dust cyclone 16 and recycled back via duct 22 to join the preheated mineral material.

[0104] The exhaust gases leave the circulating combustion chamber through a flue 10. The exhaust gases enter a first duct 11 and are quenched by quench air from a temperature between 1500°C and 1900°C (typically about 1650°C) to a temperature between 900°C and 1200°C (normally about 1100°C). Providing hot exhaust gases at a temperature above 800°C is beneficial, particularly when it is necessary to remove ammonia from the aluminium slag prior to melting.

[0105] As is known, the raw materials used as the remainder of the ore charge can be selected from a variety of sources. These include basalt, diabase, nepheline syenite, cullet, bauxite, quartz sand, limestone, borax, sodium tetraborate, dolomite, soda, olivine sand, potash. Waste materials can also be used.

[0106] MMV fibers can be made from mineral melts in a conventional manner. Typically, they are made by a centrifugal fiberization process.

[0107] For example, the fibers can be formed by a spinning rotor process, in which they are thrown outward through holes in the spinning rotor. The melt is fiberized by the spinning rotor technology (sometimes also called internal centrifugation). Before being directed to the spinning rotor, the melt preferably has a temperature in the range of 1260° C. to 1300° C. at the end of the feeder channel. When the melt is transferred from the feeder channel to the inner part of the spinning rotor, it is preferably cooled down so that the temperature of the melt when flowing through the holes of the spinning rotor is in the range of 1150° C. to 1220° C.

[0108] The viscosity of the melt in the spinning rotor is in the range of 50 Pa.s to 400 Pa.s, preferably in the range of 100 Pa.s to 320 Pa.s, more preferably in the range of 150 Pa.s to 270 Pa.s. If the viscosity is too low, fibers of the desired thickness cannot be formed. If the viscosity is too high, the melt will not flow through the holes in the spinning rotor at the correct discharge rate, which can cause the holes in the spinning rotor to become clogged.

[0109] The melt is preferably fiberized by a spinning rotor process at a temperature between 1160° C. and 1210° C. At the spinning temperature, the viscosity of the melt is preferably in the range of 100 Pa.s to 320 Pa.s.

[0110] In another fiber forming process, the melt may be thrown from a rotating disk and fiber formation may be promoted by passing a jet of injected gas through the melt.

[0111] In a preferred method, fiber formation is performed by pouring the melt onto the first rotor in a cascade spinneret. In this case, the melt is preferably poured onto the first of a set of two, three or four rotors, each rotating about a substantially horizontal axis, whereby the melt on the first rotor is primarily thrown onto the second (lower) rotor, although some may be thrown off the first rotor in the form of fibers, and the melt on the second rotor is thrown off in the form of fibers, although some may be thrown toward the third (lower) rotor, and so on.

[0112] MMVF can be collected and consolidated to form a consolidated product including MMVF. Generally, such products may include additional ingredients, such as a binder, wherein MMVF is the main ingredient. The fibers produced by the spinning process are preferably collected on a conveyor belt. The binder can be applied to the MMVF either in the fiberization process or after fiberization. The binder can be applied by spraying the MMVF. The conventional type of binder used with rock wool fibers can be used. The binder is then cured to produce a final product. The MMVF with a binder is usually cured in a curing oven, usually by a hot air stream. A hot air stream can be introduced into the MMVF with a binder from below or above or from alternating directions in different regions in the length direction of the curing oven. After curing, the cured binder composition bonds the fibers to form a fiber matrix that is structurally adhered.

[0113] The MMVF may be consolidated after collection, for example by cross-lapping and / or longitudinal compression and / or vertical compression in a known manner. Typically consolidation occurs before the binder cures.

[0114] The MMVF produced by the method of the present invention and the MMVF of the present invention have excellent fire resistance at 1000°C. The MMVF can be made into products for any conventional application of MMVF (e.g., sound insulation or heat insulation or fire protection). Such products include insulation products such as insulation wool, particles, boards, rolls, pipe sections, and other products such as tiles and loose fibers. The product can be used in high temperature environments, such as at least 400°C to as high as 1000°C.

[0115] The product may have any density known in the art for the relevant application. For example, the density may be 20 kg / m 3 Up to 300kg / m 3 All product types have advantages in terms of shrinkage, but it has been observed that when the density of the product is relatively low (e.g. not more than 50 kg / m 3 ), a particularly good reduction in shrinkage can be seen.

[0116] Any preferred feature disclosed in this application may be combined with any other preferred feature.

[0117] Example

[0118] A control sample of consolidated MMVF product was prepared from a mineral melt (control material) having the following composition:

[0119] <![CDATA[SiO2]]> <![CDATA[Al2O3]]> <![CDATA[TiO2]]> <![CDATA[Fe2O3]]> FeO CaO MgO <![CDATA[Na2O]]> <![CDATA[K2O]]> <![CDATA[P2O5]]> MnO 42,6 18,5 0,5 6,9 0,0 18,9 9,2 1,9 0,8 0,2 0,5

[0120] Table 2

[0121] The density of the manufactured control consolidated product was 30 kg / m 3 .according to Figure 1 The mineral melt is prepared in a cyclone furnace.

[0122] The consolidated MMVF product sample of the present invention was produced using MMVF spun from a feed having the composition of Table 2, to which 0.4 wt. % of aluminum particles (equivalent to 0.2 wt. % of metallic aluminum) were added. In addition to all the components listed in Table 2, the aluminum particles were added. The density of the example product was also 30 kg / m 3 .

[0123] The area shrinkage of the control product and the example product was measured according to an internal test method consisting of 5 steps:

[0124] 1) Cut, measure and weigh the test samples from the product test unit;

[0125] 2) Select representative test samples from the test unit;

[0126] 3) Remove the binder at 590°C;

[0127] 4) sintering the test sample at 1000°C + / - 20°C for 30 minutes; and

[0128] 5) Measure the area of ​​the test sample after sintering.

[0129] Shrinkage is measured as the percentage reduction in surface area of ​​each product. Shrinkage is measured on the principal surface of each product, which is the main surface that is visible in the finished product. For example, the reduction in length and width of a board is measured, but not its thickness.

[0130] Relative area shrinkage between raw material charges with and without aluminum pellets added

[0131] Sample No. Shrinkage of control sample Shrinkage of the sample of the present invention 1 87,7 72,7 2 103,6 79,0 3 83,7 75,0 4 117,6 5 107,6 Normalized mean shrinkage 100,0 75,6

[0132] Table 3 – Aluminum Pellets Test

Claims

1. A method for producing a man-made vitreous fiber (MMVF) comprising at least 3% by weight of iron oxide measured as Fe2O3, the method comprising: Provide gas furnaces, mineral raw materials, gas fuel and combustion gas, The mineral raw materials include (a) metallic aluminum and (b) other mineral components. introducing the mineral feedstock, gaseous fuel and combustion gases into the furnace, combusting the gaseous fuel to melt the mineral feedstock to form a molten pool at the base of the furnace, This forms a mineral melt, and A MMVF is formed from the mineral melt.

2. The method of claim 1 , further comprising consolidating the MMVF to form a consolidated product comprising the MMVF.

3. The method according to any one of the preceding claims, wherein the gas furnace is a canister furnace or a cyclone furnace.

4. A method according to any one of the preceding claims, comprising introducing the metallic aluminium into or directly above the molten bath.

5. The method according to claim 4, wherein the metallic aluminum is injected directly into the mineral melt.

6. The method according to any one of the preceding claims, wherein the metallic aluminum is in the form of aluminum pellets, wherein the aluminum pellets contain 45% to 100% by weight of metallic aluminum.

7. The method according to claim 6, wherein the average particle size of the aluminum particles is not greater than 3 mm.

8. The method according to any one of claims 1 to 5, wherein the metallic aluminum is in the form of one or more blocks.

9. The method of claim 8, wherein the one or more blocks are rod-shaped.

10. The method according to any of the preceding claims, wherein the MMVF has a ratio of FeO:Fe2O3 greater than 2, such as greater than 3.

11. The method according to any one of the preceding claims, wherein the MMVF has the following oxide content, in wt. %: SiO2 35 to 50 Al2O3 12 to 30 TiO2 up to 2 Fe2O3 3 to 12 CaO 5 to 30 MgO up to 15 Na2O 0 to 15 K2O 0 to 15 P2O5 up to 3 MnO up to 3 B2O3 is as high as 3.

12. The method according to any one of claims 1 to 10, wherein the MMVF has the following oxide content, in wt %: SiO2: 30 to 51 CaO: 8 to 30 MgO: 2 to 25 FeO (including Fe2O3): 4 to 15 FeO+MgO: 10 to 30 Na2O+K2O: not more than 10 CaO+Na2O+K2O: 10 to 30 TiO2: no more than 6 TiO2+FeO: 4 to 18 B2O3: no more than 5 P2O5: not more than 8 Others: 8 and above.

13. The method according to any one of claims 1 to 10, wherein the MMVF has the following oxide content, in wt %: SiO2 39% to 55%, preferably 39% to 52%, Al2O3 16% to 27%, preferably 16% to 26%, CaO 6% to 20%, preferably 8% to 18%, MgO 1% to 5%, preferably 1% to 4.9%, Na2O 0% to 15%, preferably 2% to 12%, K2O 0% to 15%, preferably 2% to 12%, R2O (Na2O + K2O) 10% to 14.7%, preferably 10% to 13.5%, P2O5 0% to 3%, preferably 0% to 2%, Fe2O3 (total iron) 3% to 15%, preferably 3.2% to 8%, B2O3 0% to 2%, preferably 0% to 1%, TiO2 0% to 2%, preferably 0.4% to 1%, Others 0% to 2.0%.